Correlation between notifiable infectious diseases and transportation passenger traffic from 2013 to 2019 in mainland China - Cuiping Xia; Jinyu Wang; Zhongxin Wang; Jilu Shen (BMC Public Health)
Abstract Purpose Population mobility significantly contributes to the spread and prevalence of infectious diseases, posing a serious threat to public health safety and sustainable development across the globe. Understanding the impact of population mobility on the prevention and control of infectious diseases holds profound significance. Methods In this study, we collected the data on the incidence of notifiable infectious diseases in mainland China from 2013 to 2019, and analyzed the characteristics of notifiable infectious diseases, as well as their correlation with transportation passenger traffic. Results Among 29 common notifiable infectious diseases, the incidence rate of intestinal diseases per 100,000 people was the highest (256.35 cases), while the mortality rate was the lowest (0.017 cases). The mortality rate per 100,000 people due to sexually transmitted and bloodborne diseases was the highest (1.154 cases). A significant linear correlation was noted between commercial passenger traffic and the number of cases of tuberculosis (r = 0.83, P = 0.022), hepatitis A (r = 0.87, P = 0.012), bacillary and amebic dysentery (r = 0.90, P = 0.006), typhoid/paratyphoid (r = 0.94, P = 0.002), leptospirosis (r = 0.90, P = 0.005), AIDS(r=-0.90, P = 0.006), gonorrhea (r=-0.79, P = 0.035) and scarlet fever (r=-0.85, P = 0.016). A significant linear correlation was noted between public transportation passenger traffic and the number of cases of measles (r = 0.94, P = 0.002), hepatitis A (r = 0.96, P = 0.001), parasitic and vector-borne diseases (r = 0.96, P = 0.001), brucellosis (r = 0.95, P = 0.001), leptospirosis (r = 0.88, P = 0.008), other infectious diarrhea (r = 0.86, P = 0.013) and gonorrhea (r = 0.84, P = 0.018). Conclusion The results of this study indicated that transportation passenger traffic significantly affected the incidence of infectious diseases, and reasonable management of passenger traffic was a potentially important means of prevention and control of infectious diseases.